Labor Analgesia Consumption and Time to Neuraxial Catheter Placement in Women With a History of Surgical Correction for Scoliosis: A Case-Matched Study. Issue 2 (June 2016) - Bauchat, Jeanette R.; McCarthy, Robert J.; Koski, Tyler R.; Wong, Cynthia A.
Abstract : ( Anesth Analg. 2015;121:981–987) Though neuraxial analgesic techniques are known to be more effective than other types of labor analgesia, some small studies in the past have shown these techniques to be only effective in 50% to 66% of patients who have undergone surgical correction for scoliosis. Although it has become easier to access the epidural space due to recent developments in surgical interventions for scoliosis, the effectiveness of neuraxial labor analgesia can still be diminished by postsurgical scarring and adhesions. The authors sought to carry out a prospective case-matched study to compare the rate of bupivacaine consumption and time to placement of neuraxial technique between laboring women with and without a history of spinal instrumentation.